(untitled) (Fiep Bulletin - online, 2012)
The objective of this research was to describe the epidemiology of infectious diseases in the population from 0 to 12 years, admitted in 2009 and 2010 Hospital Dr. Rafael Fernandes, in Mossoró / RN. It is a descriptive, documental, retrospective and quantitative approach was based on the records of children aged 0 to 12 years admitted with infectious diseases in the HRF in the years 2009 and 2010. Data were analyzed using Excel 2007 and arranged in graphics. Data were collected after approval by the Ethics Committee in Research of the University with Potiguar Protocol 162/2010, CAAE: 0166.0.052.000-10. In 2009, 58% of children aged between 0 and 6 years, 42% between 7 and 12 years. In 2010, 55% of children between 0 and 6 years, 45% were between 7 and 12 years. Regarding the economic situation of families of children affected by these diseases in 2009 is that 57% of households have incomes between 1 and 2 minimum wages, 6% income above 2 minimum wages, and 37% have no fixed income . In the year 2010 is that 60% of households have incomes between 1 and 2 minimum wages, 5% of households, more than two minimum wages, and 35% no fixed income. The main infectious diseases recorded in the HRF, for 2009 are 60% visceral leishmaniasis; chickenpox 11% 6% meningitis, 14% classic dengue, dengue hemorrhagic 8%, others 11%. The results for 2010 show that 50% of visceral leishmaniasis, meningitis 20%, hepatitis 15%, 5% and chickenpox. The data allowed us to realize that even with all the advancement of science and technology in the health sector to combat the infectious diseases still constitutes a major challenge.